GE_GERICHTE P/15240/2008 vom 26. Mai 2009 - GE Cour de justice (2009)
RÉVISION(DÉCISION);EXPERTISE PSYCHIATRIQUE;MESURE THÉRAPEUTIQUE INSTITUTIONNELLE | CPP.410.al1.leta; CPP.412; CPP.132.al1.letb; CP.59